2020
DOI: 10.1016/j.physd.2020.132495
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven predictions of the Lorenz system

Abstract: This paper investigates the use of a data-driven method to model the dynamics of the chaotic Lorenz system. An architecture based on a recurrent neural network with long and short term dependencies predicts multiple time steps ahead the position and velocity of a particle using a sequence of past states as input. To account for modeling errors and make a continuous forecast, a dense artificial neural network assimilates online data to detect and update wrong predictions such as non-relevant switchings between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…And it is indeed so, but quite often the predictions are not correct and this can significantly impact the performance of the trading strategy. However, it has been shown that some techniques exist which can predict even quasi-periodic time-series, which is quite remarkable, considering the fundamentally chaotic nature of such time-series [29,30]. Depending on the nature of the time-series, the prediction interval is generally one time-step and for each new time-point prediction, the ground truth is fed back to the network.…”
Section: Predictionmentioning
confidence: 99%
“…And it is indeed so, but quite often the predictions are not correct and this can significantly impact the performance of the trading strategy. However, it has been shown that some techniques exist which can predict even quasi-periodic time-series, which is quite remarkable, considering the fundamentally chaotic nature of such time-series [29,30]. Depending on the nature of the time-series, the prediction interval is generally one time-step and for each new time-point prediction, the ground truth is fed back to the network.…”
Section: Predictionmentioning
confidence: 99%
“…It is, indeed, so, but quite often the predictions are not correct, and this can significantly impact the performance of the trading strategy. However, it has been shown that some techniques exist which can predict even quasi-periodic timeseries, which is quite remarkable, considering the fundamentally chaotic nature of such time-series [29,30]. Depending on the nature of the time-series, the prediction interval is generally one time-step, and for each new time-point prediction, the ground truth is fed back to the network.…”
Section: Predictionmentioning
confidence: 99%
“…In addition, because it was possible that these two types would do better at replicating specific aspects of the overall solution, we also evaluated a superposition of the two. Time series surrogates often use recurrent NN (Zhang and Xiao, 2000 ; Dubois et al, 2020 ). Similarly, deep generative models have been shown to be useful to sample from high dimensional space, as in the case of molecular dynamics and chemical reaction modeling (Chen and Ferguson, 2018 ; NoĂ© et al, 2019 , 2020 ; Zhang et al, 2019 ; Gkeka et al, 2020 ; Kasim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%